Chemical foaming of polylactic acid/polypropylene and polylactic acid/polyamide 6: Evaluation of changes in their properties - Tuna, Sibel; Akkoyun Kurtlu, Meral (Journal of thermoplastic composite materials, 2024)
Most of the polymers made from fossil fuels end up as waste material and this environment-damaging situation has revealed the need to take some precautions such as the use of eco-friendly, biodegradable materials obtained from renewable sources as an alternative. Biopolymers are being evaluated as alternatives to traditional polymers especially in the automotive industry due to their better-understood properties such as mechanical and physical behavior through the studies conducted. On the other hand, when the literature studies are evaluated, it can be seen that the production of foam materials, which are focused on lightness and carbon dioxide (CO2) emission limitations that are important and essential for the automotive sector, is an area that is also researched and studied for biopolymers. Several studies are carried out with both physical and chemical foaming agents on this subject in recent years. In this study, it is aimed to develop light, environmentally friendly, high-performance polylactic acid (PLA) based polymeric composite foams that can be used in the automotive industry by using twin screw extruder and compression molding methods. For this purpose, polyamide 6 (PA6) and polypropylene (PP) polymers were used with PLA and by adding 1 wt.%, 1.5 wt.% and 2 wt.% chemical blowing agents to the polymer mixtures, the physical, thermal, mechanical, morphological properties and changes in these properties were investigated. The most suitable chemical blowing agent ratio was found to be 1.5 wt.% for PLA/PP and PLA/PA6 mixtures.